0428 Insomnia And Stress: Associations With Mental Resilience And Mood. (27th April 2018) - Verster, J C; Palagini, L; Mackus, M; van de Loo, A J; Garssen, J; Roth, T
Abstract: Introduction: The aim of this study was to investigate the association between insomnia symptoms, psychological health, mental resilience, and stress. Methods: A survey was held among young Dutch adults, aged 18 to 30 years old. The insomnia subscale of the SLEEP-50 questionnaire was completed. In addition, prior night's bedtime, time of sleep onset, and arising time were recorded. Psychological wellbeing was assessed using the 5-item World Health Organization (WHO-5) Well-Being Index and mental resilience was assessed using the Brief Resilience Scale. Mood was assessed with the short-form Profiles of Mood States (POMS-SF), and the Depression Anxiety Stress scale (DASS) and Eysenck personality questionnaire scales of extraversion and neuroticism were completed. Insomnia scores were associated with sleep and mood and personality outcomes. In addition, mood and personality of those who screen positive for insomnia (score > 19) were compared to those who score negative for insomnia. Results: N=2489 subjects completed an online survey. Of them, 83.4% were women (N=2075). Insomnia score correlated significantly (p<0.0001) with sleep quality (r =-0.720), number of nightly awakenings (r = 0.489), and sleep onset latency (r = 0.552), but not with total sleep time. The insomnia score correlated significantly with all psychological, mood and health assessments (p<0.05). Those who screened positive for insomnia (i.e. a score>19) scored significantly lower (p<0.0001) on general health, wellbeing, and mental resilience, extraversion, and the POMS-SF mood scale vigor-activity. They scored significantly higher on the DASS stress, anxiety and depression scales, neuroticism, and the POMS-SF mood scales tension-anxiety, depression, anger-hostility, and fatigue. The observed differences and associations were significantly more pronounced in women when compared to men. Conclusion: Insomnia is associated with poorer psychological health and mood, reduced metal resilience, and increased levels of stress, anxiety and depressive symptoms. Support (If Any):